Could the negative capacitance effect be used in field-effect transistors with a ferroelectric gate? - Eliseev, E. A.; Morozovska, A. N.; Yurchenko, L. P.; Strikha, M. V. (Physics and Chemistry of Solid State, 2022)
We analyze the electric potential and field, polarization and charge, and differential capacitance of a silicon metal-oxide-ferroelectric field effect transistor (MOSFET), in which a gate insulator consists of thin layers of dielectric SiO2 and weak ferroelectric HfO2. It appeared possible to achieve a quasi-steady-state negative capacitance (NC) of the HfO2 layer, , if the layer thickness is close to the critical thickness of the size-induced ferroelectric-paraelectric phase transition. However, this effect disappears as the gate voltage increases above a certain critical value, which can be explained by the nonlinearity of the ferroelectric permittivity. The quasi-steady-state NC corresponds to a positive capacitance of the whole system. Implementation of the gate insulator NC, , can open the principal possibility to reduce the MOSFET subthreshold swing below the critical value, and to decrease the gate voltage below the fundamental Boltzmann limit. However, we failed to found the parameters for which is negative in the quasi-steady states; and thus, the negative cannot reduce the subthreshold swing below the fundamental limit. Nevertheless, the increase in , related with , can decrease the swing above the limit, reduce device heating during the operation cycles, and thus contribute to further improvements of MOSFET performances.